If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(m + -3) = 8m + -40 Reorder the terms: 4(-3 + m) = 8m + -40 (-3 * 4 + m * 4) = 8m + -40 (-12 + 4m) = 8m + -40 Reorder the terms: -12 + 4m = -40 + 8m Solving -12 + 4m = -40 + 8m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-8m' to each side of the equation. -12 + 4m + -8m = -40 + 8m + -8m Combine like terms: 4m + -8m = -4m -12 + -4m = -40 + 8m + -8m Combine like terms: 8m + -8m = 0 -12 + -4m = -40 + 0 -12 + -4m = -40 Add '12' to each side of the equation. -12 + 12 + -4m = -40 + 12 Combine like terms: -12 + 12 = 0 0 + -4m = -40 + 12 -4m = -40 + 12 Combine like terms: -40 + 12 = -28 -4m = -28 Divide each side by '-4'. m = 7 Simplifying m = 7
| 10=x+5-2x | | y-10=37 | | 14y^2=18 | | 7y+9+3y+9=143 | | a+17=-19 | | -4.5a=-32.4 | | -(5/9)k=2 | | x+56=x-23 | | 7x+9=4x+12 | | a+19=-17 | | (10t-5t+14)+(11t-8)= | | 5y+14-8y=-20 | | 7w-4w-3=12 | | 0.7x-0.3x+5=7 | | 3x=450 | | 84=20x | | 3x+4x-8=2(2x+5) | | 2x=8x+2 | | 3y^2-16y+20=0 | | -12=-6x+2(x-4) | | -9z=9 | | 3.2=1.4+x | | 3x-8=2x+17 | | -v+2v+6=-3 | | 24x+18y= | | 3y+12=2y | | 2x^2-8x+2y^2+20y=12 | | 3s+9=2(s-6) | | 3x-8+2x+17= | | 5x+3x+12=28 | | 3x+5(2)=10 | | 3(7+3x)=3(x-3) |